2008
DOI: 10.1093/rpd/ncn024
|View full text |Cite
|
Sign up to set email alerts
|

Patient dose in interventional radiology: a European survey

Abstract: Patient doses for a few common fluoroscopy-guided procedures in interventional radiology (IR) (excluding cardiology) were collected from a few radiological departments in 13 European countries. The major aim was to evaluate patient doses for the basis of the reference levels. In total, data for 20 procedures for about 1300 patients were collected. There were many-fold variations in the number of IR equipment and procedures per population, in the entrance dose rates, and in the patient dose data (total dose are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 5 publications
4
44
2
1
Order By: Relevance
“…To provide adequate radiation dose data, due the large individual variability of patient dose in fluoroscopically guided interventional procedures, Vano et al [22] recommended to collect the radiation data of >50 patients within the same type of procedure for a single center. In this study, the number of cases per type of procedures was >50 for all categories, except for AVF/AVM.…”
Section: Discussionmentioning
confidence: 99%
“…To provide adequate radiation dose data, due the large individual variability of patient dose in fluoroscopically guided interventional procedures, Vano et al [22] recommended to collect the radiation data of >50 patients within the same type of procedure for a single center. In this study, the number of cases per type of procedures was >50 for all categories, except for AVF/AVM.…”
Section: Discussionmentioning
confidence: 99%
“…Vano et al [16] found 3 rd quartile values of P KA and fluoroscopy time for the diagnostic procedure cerebral angiography of 107 Gycm 2 and 12 minutes. They also suggest preliminary reference levels for this procedure of 120 Gycm 2 and 15 minutes based also on the other five references quoted in their publication.…”
Section: Tablementioning
confidence: 98%
“…But is has also been suggested for use in interventional cardiology [15]. Others [16][17][18] have also suggested using P KA as an indicator for high skin doses.…”
Section: Introductionmentioning
confidence: 99%
“…The DAP is measured through an ionization chamber located in the front of the collimator, and the measured values are transferred via DICOM. In Europe, The DAP is considered the reference value and is compared with the measured radiation exposures of patients undergoing interventional radiological procedures [12].…”
Section: Radiation Dose Monitoringmentioning
confidence: 99%